INITIAL ASSESSMENT IN COUNSELING - Irma, Irma Suryani Nasution; Mona, Lisa Sis; Fitriani, Wahidah (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2024)
The purpose of this study is to enrich knowledge about initial assessment in counseling. This research method uses qualitative with a literature study approach. Data sources are obtained from Google Scholar in the form of books and articles. In-depth data analysis related to research materials. The results of the study, namely the evaluation steps taken by counselors when conducting counseling sessions with clients for the first time, are very important because through the implementation of initial evaluations, counselors can gain an understanding of clients and the problems they face.